Tingkat Pengetahuan Mahasiswi Program Studi Diploma Tiga Keperawatan Tingkat I di STIKes Panti Rapih tentang Upaya Pencegahan Infeksi Saluran Kemih - Ayunita Yunda Prastiwi; MI Ekatrina Wijayanti (I Care Jurnal Keperawatan STIKes Panti Rapih, 2020)
Background: Urinary Tract Infections (UTIs) are infections caused by the growth of bacteria in the urinary tract. UTIs are caused by Escherichia Coli. Continous infection will reach the ureter and kidney which caudes infection in the kidney parenchyma. Objective: The purpose of this study was to determine the level of knowledge of Nursing Diplola level 1 students at STIKes Panti Rapih. Methods: This study was descriptive quantitative survey method. The sample was 65 female students, and using total sampling. Results: Study found that most of the students were aged 18 years old (73.88%). 58 respondents never participate in consultation about UTIs (89,23%) and 7 respondents (10,76%) had participate in education. 30 respondent (36,92%) with high knowledge, 30 (46,15%) morderate knowledge, and 11 (16,92%) low knowledge. Conclusion: Concluded that the level of knowledge nursing students diploma of STIKes Panti Rapih to prevent urinary tract infections less than half percent were morderate. Keywords: Urinary Tract Infection, level of knowledge, students